Assessment of Psychological Impact among Hospitalized Children; Single Centre Study - Abd Elhamid, Salwa Amin; Abdelaziz, Eman Amin; Youssef, Azza Mohamed; Mahmoud, Mennat Allah Zakaria; Abdel Raouf, Batoul Mohamed (International Journal of Child Health and Nutrition, 2024)
Background: The goal of the contemporary hospital setting is to give patients suffering from a range of diseases a secure and therapeutic space. Aim: Psychosocial and mental health assessment among hospitalized children between 7 to 12 years of age. Methods: This Cross-Sectional Study was carried out at the Children's Hospital Faculty of Medicine for 1-year duration. Results: Higher statistically significant positive results were found in cases than in control regarding all Vanderbilt subscales except in the conduct subscale. Higher results were found in chronic cases than control in all subscales except for oppositional defiant disorder results. Conclusion: Hospitalized Children, due to chronic or acute conditions, are at a higher risk for Psychosocial and mental health disorders such as depression, anxiety, ADHD, PTSD, and pain in comparison with healthy children.